PENGARUH AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT.POS INDONESIA (PERSERO) KANTOR CABANG UTAMA BANDUNG - Fitrilia Diah Ayu Erlina; Widwi Handari Adji (Media Bina Ilmiah, 2023)
The purpose of this study was to determine the extent of the influence of human resource management audits on employee performance at PT Pos Indonesia (Persero) at the Bandung Head Office. The method used by researchers is quantitative, where the data collection method is to distribute questionnaires through Google Form to 55 employees who are respondents, the data obtained is then analyzed with the SPSS V.25 program. The results of this study indicate that "The Effect of Resource Management Audit on Employee Performance of PT Pos Indonesia (Persero) Bandung Main Branch Office" has a significant effect on employee performance. Based on the data from the coefficient of determination test results, this explains the amount of correspondence (R- squared) which is 0.955 or 95.5%. The results of the influence of human resource management audits on employee performance at pt.pos indonesia (persero) main branch office bandung, the results of the output are said to be very influential on human resource management audits on employee performance.